A consolidated catalogue of jovian decametric radio observations observed in Nançay from January 1978 to December 1990 - Cecconi, B.; Debisshop, L.; Lamy, L.; Genova, F. (My University, 2023)
A series of five Jovian decametric radio emission catalogues covering 13 years of observations (1978 to 1990) and published between 1981 and 1993 has been compiled after a digitisation process. The new catalogue has been validated and is provided in a standardised and interoperable format. In addition to the well-known Io–controlled Jovian radio emissions components, the catalogue statistically confirms the control by Ganymede.